Step-by-step explanation
We are asked to solve the given quadratic equation
![2x^2+3x-20=0](https://img.qammunity.org/2023/formulas/mathematics/college/mwt7iqj6gqz51nwoihelkxxyuxog4c608y.png)
To do so, we will have to find the factors of the product of the coefficient of the first and last term whose sum is 3
Thus
![2*-20=-40](https://img.qammunity.org/2023/formulas/mathematics/college/5tuitt37swqr8dvgz11fg2kq0hbyexnijt.png)
So the factor of -40 which also gives a sum of 3 will be
![8\text{ and -5}](https://img.qammunity.org/2023/formulas/mathematics/college/t0279yfn6v1nlea7wkr22nz69khv3lqd0c.png)
Thus
![\begin{gathered} 2x^2+8x-5x-20=0 \\ 2x(x+4)-5(x+4)=0 \\ (2x-5)(x+4)=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/1lrldzwvjon9qw6jrwnvrchmflnjgfpbb1.png)
We will have the answer will be
![(2x-5)(x+4)](https://img.qammunity.org/2023/formulas/mathematics/college/3hhn305pz0srlo2zbjyc27gio5dppt4t6x.png)
Simplifying further
we will have the zeros to be
![\begin{gathered} 2x-5=0 \\ x=(5)/(2)=2.5 \\ \\ \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/4ty7cyo8u5uixallek5xy7hg4phoayj43u.png)
Also
![\begin{gathered} x+4=0 \\ x=-4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ahfro6vgi1du23qi2v6ipejq86lwadp7sw.png)
So the answers are:
x = -4 and x= 5 over 2